O Impacto da Técnica de Alexander na prática do canto: um estudo qualitativo sobre as percepções de cantores com experiência nessa interação - Paulo Henrique Campos Silva (2007)
This study investigates the potential benefits of the Alexander Technique for the development of singers. The study adopts a literature review which includes an anatomic-physiological description of the organs and mechanisms that form the vocal equipment, as well as the principles and theoretical foundations of the Alexander Technique and its connection with singing. To obtain information about the connections between the Alexander Technique and singing, semi-structures interviews were conducted with five singers, who also are Alexander practitioners. The data provided by them were analyzed according to the categories established in the literature review, which provided the parameters related to both areas singing and the Alexander Technique. The analysis results allow us to suggest that theAlexander Technique may have a fundamental role in the establishment of a new and healthier relation of the singer with his or her vocal equipment in diverse levels: breathing, vocal support, vocal quality and vocal projection, anxiety, tension, effort and expressivity. The Alexander Technique makes it possible for singers to overcome their vocal problems and limitations, generated by the bad use of the organism which may be unconsciously adopted by singers. In this way, the Alexander Technique may improve the vocal functioning of singers and provide to them a better quality of life.